Identification of 2, 4‐Dinitro‐Biphenyl‐Based Compounds as MAPEG Inhibitors. (11th October 2022) - Di Micco, Simone; Terracciano, Stefania; Pierri, Martina; Cantone, Vincenza; Liening, Stefanie; König, Stefanie; Garscha, Ulrike; Hofstetter, Robert Klaus; Koeberle, Andreas; Werz, Oliver; Bruno, Ines; Bifulco, Giuseppe
Abstract: We identified 2, 4‐dinitro‐biphenyl‐based compounds as new inhibitors of leukotriene C4 synthase (LTC4 S) and 5‐lipoxygenase‐activating protein (FLAP), both members of the "Membrane Associated Proteins in Eicosanoid and Glutathione metabolism" (MAPEG) family involved in the biosynthesis of pro‐inflammatory eicosanoids. By molecular docking we evaluated the putative binding against the targets of interest, and by applying cell‐free and cell‐based assays we assessed the inhibition of LTC4 S and FLAP by the small molecules at low micromolar concentrations. The present results integrate the previously observed inhibitory profile of the tested compounds against another MAPEG member, i. e., microsomal prostaglandin E2 synthase (mPGES)‐1, suggesting that the 2, 4‐dinitro‐biphenyl scaffold is a suitable molecular platform for a multitargeting approach to modulate pro‐inflammatory mediators in inflammation and cancer treatment. Abstract : Multipronged strategy : 2, 4‐Dinitro‐biphenyl‐based compounds were identified as inhibitors of leukotriene C4 synthase (LTC4 S) and 5‐lipoxygenase‐activating protein (FLAP), both members of the "Membrane Associated Proteins in Eicosanoid and Glutathione metabolism" (MAPEG) family involved in the biosynthesis of pro‐inflammatory eicosanoids. The results of this study show the 2, 4‐dinitro‐biphenyl scaffold to be suitable for a multitarget approach to modulate pro‐inflammatory mediators in inflammation and cancer treatment.